Does Customer Satisfaction and Service Quality have an impact on HDFC Bank Customers’ Loyalty? - Jyoti; Kaur, Dr. Rupinder Bir (Gyan Management Journal, 2023)
Purpose- The purpose of the present study is to investigate the service quality of HDFC Bank and how it affects the satisfaction and loyalty of their customers. Finding out how customer satisfaction affects service quality and customer loyalty among HDFC customers is the study’s secondary goal. Design/Methodology/Purpose -Using a questionnaire-based survey method, data from 120 bank customers were gathered using the Purposive Sampling method. Of these, 55.5 per cent were female and 44.5 per cent were male.Findings- The study’s findings showed a significant link between customer satisfaction and service quality (H1). Results, however, indicate that HDFC Bank customer loyalty is not significantly influenced by service quality and customer satisfaction (H2, H3). Additionally, this study’s findings indicate that there is no conclusive evidence linking customer loyalty and service quality through customer satisfaction as a mediator (H4). Research limitations/Implications- Results may vary in other countries and generalizability to the full population is constrained. Future studies will use more varied samples or carry out more comparable investigations in different sectors.Practical Implications- The study’s findings showed that client loyalty cannot be assured by customer satisfaction and service quality alone.